PERANAN GENDER DALAM ADAPTASI PERUBAHAN IKLIM PADA EKOSISTEM PEGUNUNGAN DI KABUPATEN SOLOK, SUMATERA BARAT - Yanto Rochmayanto; Pebriyanti Kurniasih (Jurnal Analisis Kebijakan Kehutanan, 2013)
Climate change causes abominable impact to woman, but the study of gender adaptation perpectives is still very limited. The objectives of the research were to know: (1) changes in gender roles that emerged as a response to climate change, and (2) impact of changes in gender roles on woman'sv ulnerability.The research was conducted at mountain ecosystem in Solok Regency, West Sumatera. The gender role in natural resources management is analyzed using descriptive analysis method which emphasizes gender relationship and gender roles that are formed in the house hold. The results showed that changes in temperature and rain fall patternsare slowly changing the productive role that woman participated in the agriculture production responsibility in a larger proportion. Changes in gender roles raises gender untillness in the farms of marginalization, stereotypes, subordination, and adouble burden for woman. To enhance the adaptive capacity for woman, it is required to develop the adaptation strategies covering:(1) to increase the political role of woman,(2) to increase the capacity of woman in formal and informal education, and (3) cultural reconstruction based on gendere quality